The Near Sovereign Apothecary’s Order - V. G. Abashin; P E. Krynyukov; V. B. Simonenko; P. A. Dulin (Clinical Medicine (Russian Journal), 2026)
The article provides information about the creation and operation of the Pharmacy Order, the main directions of its work. Information is provided on the structures that preceded the Pharmacy Order and were created based on it later. The names of the leaders of the Pharmaceutical Leprosy are given and some biographical information is provided.